2021
DOI: 10.1177/00953997211041131
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Spirit of the Sectors: Exploring Identity in a New Era of Organizing

Abstract: While sector distinction debates often re-emerge during periods of cultural and institutional upheaval, none have considered an identity-orientation perspective. Identity orientation is a natural domain in which to address these debates as it considers the individualistic, relational, and collectivistic foundations of organizations. This study explores whether organizational members across sectors view their organization’s identity orientation differently. Findings suggest that member perceptions of identity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 107 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…However, not all managers will perceive the same pressures regardless of sector. As the identity (Langer, 2022) or degree of publicness (Min et al 2020) of the organizations partnering have been found to influence collaboration, so too may the existence or perception of deterrent pressures. In our study, the finding of deterrent pressures clarified the distinction between coordinators and collaborators, and moreover supports the importance of investigating the existence and source of both supportive and deterrent pressures when investigating the effects of perceived isomorphic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all managers will perceive the same pressures regardless of sector. As the identity (Langer, 2022) or degree of publicness (Min et al 2020) of the organizations partnering have been found to influence collaboration, so too may the existence or perception of deterrent pressures. In our study, the finding of deterrent pressures clarified the distinction between coordinators and collaborators, and moreover supports the importance of investigating the existence and source of both supportive and deterrent pressures when investigating the effects of perceived isomorphic pressures.…”
Section: Discussionmentioning
confidence: 99%